Santri, Kyai, dan Pesantren (Studi Kasus: Kemenangan Pasangan Ganjar Pranowo-Taj Yasin pada Pilgub Jateng 2018) - -, Sihono -; -, Fitriyah - (Journal of Politic and Government Studies, 2020)
The openness of the electoral system allows the involvement of various instruments to carry out political mobilization, including non-party instruments. The 2018 Central Java Governor Election is an example of the involvement of non-party instruments formed through the social capital of the Al Anwar Sarang Islamic Boarding School santri network, Rembang which supports Ganjar-Yasin pair. This role is generally carried out by political parties that have the role of mobilizing the masses, in which the santri network is also involved in mass mobilization. Therefore, this study aims to explain the use of the santri network as a political machine in governor election contestation. The research method used in this research uses descriptive qualitative research methods, with data collection techniques through interviews. The data obtained were then analyzed with secondary data obtained through books and previous research results. The results showed that the role of Kyai and network figures was a contributing factor to the victory of the Ganjar-Yasin pair in Rembang Regency and in santri-based areas that had a link with Al Anwar Islamic Boarding School. Through the role of the Kyai who has strong ties to the santri and community, a patron client pattern is formed with the Kyai encouraging followes to follow the Kyai’s political orientation. In addition, the social capital of the Al Anwar Islamic Boarding School santri network served as a political machine by introducing the programs of the Ganjar-Yasin pair. The recognition carried out by the santri network used a direct selling approach, namely through religious recitations and Islamic assemblies. The use of the santri network as a political machine has an effect on the expenditure of election costs, which are known to be expensive so that this method should be applied to the other prospective candidates who come forward in the election.